2011
DOI: 10.1080/19325037.2011.10599176
|View full text |Cite
|
Sign up to set email alerts
|

Drinking to Get Drunk Among Incoming Freshmen College Students

Abstract: This study examined college freshmen who intentionally drink alcohol to get drunk (DTGD). Survey data from 307 incoming freshmen college students living in freshmen residence halls who reported drinking alcohol in the last 30 days were analyzed. The majority (76.9%) of these self-reported drinkers reported DTGD. Relative to other freshmen drinkers, those who reported DTGD were significantly more likely to have consumed alcohol before going out to a party or bar, participated in a drinking game, drank heavily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
0
21
0
2
Order By: Relevance
“…Other motives seem to influence alcohol consumption and levels of intoxication while gaming. For example, students who drink to get drunk (Boekeloo et al, 2011) or play drinking games to show they can hold their liquor (Hone et al, 2013) are more likely to frequently drink alcohol as part of a drinking game and consume more alcohol while gaming, respectively. Students who reported playing drinking games for fun and celebratory reasons tended to also report high levels of inebriation when they participated in verbal (e.g., never have I ever), ping pong (e.g., beer pong), card (e.g., kings), speed (e.g., flip cup), or coin (e.g., quarters) games compared with drinking versions of board games like Monopoly or Cranium (Zamboanga, Calvert, et al, 2007).…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…Other motives seem to influence alcohol consumption and levels of intoxication while gaming. For example, students who drink to get drunk (Boekeloo et al, 2011) or play drinking games to show they can hold their liquor (Hone et al, 2013) are more likely to frequently drink alcohol as part of a drinking game and consume more alcohol while gaming, respectively. Students who reported playing drinking games for fun and celebratory reasons tended to also report high levels of inebriation when they participated in verbal (e.g., never have I ever), ping pong (e.g., beer pong), card (e.g., kings), speed (e.g., flip cup), or coin (e.g., quarters) games compared with drinking versions of board games like Monopoly or Cranium (Zamboanga, Calvert, et al, 2007).…”
Section: Review Of Current Literaturementioning
confidence: 99%
“…One explanation for heavy drinking among college students is that it often is seen as a type of rite of passage for students. As such, it is something students tend to regard as acceptable and normative behavior (Boekeloo, Novik & Bush 2011; Crawford & Novak 2006). Despite its apparent acceptance, heavy drinking can result in various adverse consequences, such as injurious accidents, sexual abuse, fighting, and even death (Hingson et al 2002).…”
mentioning
confidence: 99%
“…Further, Tomaso et al (2013) found that high schoolers who reported current participation in both DGs and prepartying endorsed enhancement motives more frequently than those who only played DGs and those who did not participate in either activity. Finally, in terms of studies with samples of incoming college students, Boekeloo, Novik, and Bush (2011) suggest that students who report drinking to get drunk are at increased risk for consuming alcohol as part of playing DGs. Another study by Borsari et al (2003) found that the most commonly endorsed motive for playing DGs among incoming college students was to get drunk quickly (endorsed by 55% of the sample), followed closely by playing to socialize/meet new people (endorsed by 53% of the sample).…”
Section: Literature Reviewmentioning
confidence: 99%